A new morphinandienone alkaloid from the stems of Fissistigma tungfangense. Issue 3 (1st February 2019) - Zhou, Qi; Fu, Yan-Hui; Zhang, Yu-Qin; Wu, Shou-Yuan; Song, Xiao-Ping; Xu, Wei; Chen, Guang-Ying
Abstract: A new morphinandienone alkaloid, fissistigmine A (1 ), together with three known alkaloids (2 −4 ), were isolated and identified from the stems of Fissistigma tungfangense . Among them, fissistigmine A (1 ) represents the first example of a novel naturally occurring morphinandienone alkaloid with a unique cleavage of the C-9−N-17 bond. All isolated compounds were evaluated for their anti-rheumatoid arthritis activities via examining their anti-proliferative effects on synoviocytes in vitro . Compound 1 exhibited inhibitory effect on the proliferation of synoviocytes with an IC50 value of 114.6 ± 2.2 μM. Abstract :